2020
DOI: 10.1007/s00125-020-05334-x
|View full text |Cite
|
Sign up to set email alerts
|

The liver–alpha cell axis associates with liver fat and insulin resistance: a validation study in women with non-steatotic liver fat levels

Abstract: Aims/hypothesis Many individuals who develop type 2 diabetes also display increased glucagon levels (hyperglucagonaemia), which we have previously found to be associated with the metabolic syndrome. The concept of a liver–alpha cell axis provides a possible link between hyperglucagonaemia and elevated liver fat content, a typical finding in the metabolic syndrome. However, this association has only been studied in individuals with non-alcoholic fatty liver disease. Hence, we searched for a link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
10
27
0
Order By: Relevance
“…Our data also potentially reconcile the observations that NAFLD is associated with both an increase in hepatic cholesterol (Min et al, 2012;Puri et al, 2007) and glucagon resistance (Albrechtsen et al, 2018;Gar et al, 2021). Contrasting with the possibility discussed above, i.e.…”
Section: Class B Gpcr Structures With Modelled Cholesterolsupporting
confidence: 87%
See 1 more Smart Citation
“…Our data also potentially reconcile the observations that NAFLD is associated with both an increase in hepatic cholesterol (Min et al, 2012;Puri et al, 2007) and glucagon resistance (Albrechtsen et al, 2018;Gar et al, 2021). Contrasting with the possibility discussed above, i.e.…”
Section: Class B Gpcr Structures With Modelled Cholesterolsupporting
confidence: 87%
“…To date, the mechanism behind this phenomenon is incompletely understood (Janah et al, 2019). Hepatic cholesterol accumulation is a feature of NAFLD and, interestingly, the degree of both glucagon resistance (Gar et al, 2021) and hepatic cholesterol accumulation (Min et al, 2012;Puri et al, 2007) are correlated with histological severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Support for this theory comes from the ADDITION-PRO study, as circulating levels of amino acids (alanine, glutamine, and tyrosine) associated with fasting glucagon in 1408 adults with normal and impaired glucose tolerance ( 38 ). These findings were replicated in an independent cohort of women with low to high risk for type 2 diabetes, where even lower levels of liver fat % were associated with hyperglucagonemia, reflecting impairments of the liver–alpha cell axis ( 39 ). It is hypothesized that a similar relationship may exist in youth, since the present study found a positive association between fasting glucagon, liver fat %, and ALT.…”
Section: Discussionmentioning
confidence: 78%
“…The role of GCGN in the dysregulation of glucose and lipid metabolism is debated at present ( 5 , 10 , 15 ). GCGN is consistently elevated in people with fatty liver and T2DM and contributes to hyperglycemia as shown with GCGN antagonists ( 27 , 28 ). However, GCGN antagonists increased dyslipidemia, IHL and liver enzymes ( 13 ).…”
Section: Discussionmentioning
confidence: 98%